2022
DOI: 10.3390/ijerph19052871
|View full text |Cite
|
Sign up to set email alerts
|

Three-Month vs. One-Year Detraining Effects after Multicomponent Exercise Program in Hypertensive Older Women

Abstract: Background: Chronic diseases are the leading causes of death and disability in older women. Physical exercise training programs promote beneficial effects for health and quality of life. However, exercise interruption periods may be detrimental for the hemodynamic and lipidic profiles of hypertensive older women with dyslipidemia. Methods: Nineteen hypertensive older women with dyslipidemia (exercise group: 67.5 ± 5.4 years, 1.53 ± 3.42 m, 71.84 ± 7.45 kg) performed a supervised multicomponent exercise trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…Interesting, Timmons et al [ 48 ] did not find decreases in the handgrip muscle strength as well as in other specific outcomes related to functionality in older adults, such as gait velocity, sit to stand, and timed up-and-go tests. After 9 months of the exercise training programme in older adults (endurance exercise 15–25 min, RT 15–20 min), followed by 12 months of no exercise/detraining, Leitão et al [ 49 ] reported that older adults with a significant loss in body weight of Δ − 1.9% during training recovered Δ + 0.64%, those with a decrease of Δ − 2.4% in body fat recovered Δ + 1.1%, those with a decrease of Δ − 5.1/− 5.2% in SBP/DBP recovered Δ + 7.8% in SBP/DBP, respectively, during the detraining period, those with a Δ − 16.4% decrease in Tg recovered Δ + 7.2%, and those with a Δ − 15.2% decrease in FPG after training had recovered Δ + 19.3% after the detraining period. Additionally, both upper- and lower-body muscle strength increased after the training period (Δ + 30.3/+ 30.6%); unfortunately, after 12 months of exercise cessation, both had worsened, participants losing Δ − 12.7/ − 11.6% of muscle strength in each upper- and lower-body compound, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, Timmons et al [ 48 ] did not find decreases in the handgrip muscle strength as well as in other specific outcomes related to functionality in older adults, such as gait velocity, sit to stand, and timed up-and-go tests. After 9 months of the exercise training programme in older adults (endurance exercise 15–25 min, RT 15–20 min), followed by 12 months of no exercise/detraining, Leitão et al [ 49 ] reported that older adults with a significant loss in body weight of Δ − 1.9% during training recovered Δ + 0.64%, those with a decrease of Δ − 2.4% in body fat recovered Δ + 1.1%, those with a decrease of Δ − 5.1/− 5.2% in SBP/DBP recovered Δ + 7.8% in SBP/DBP, respectively, during the detraining period, those with a Δ − 16.4% decrease in Tg recovered Δ + 7.2%, and those with a Δ − 15.2% decrease in FPG after training had recovered Δ + 19.3% after the detraining period. Additionally, both upper- and lower-body muscle strength increased after the training period (Δ + 30.3/+ 30.6%); unfortunately, after 12 months of exercise cessation, both had worsened, participants losing Δ − 12.7/ − 11.6% of muscle strength in each upper- and lower-body compound, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With these shortcomings in mind, we undertook a subsequent meta-analysis, specifically addressing multi-component exercise training (see also Supplementary Material). Based on the available evidence ( n = 4) ( 35 , 39 , 40 , 44 ), the results of the timed up and go test indicate a difference of −0.26 s (95% CI −0.66 to 0.14) between the multi-component exercise training group and the no exercise training group. In simpler terms, a combination of aerobic and resistance exercise ( 39 , 40 ), or aerobic and functional exercise ( 35 , 44 ), did not improve balance or reduce fall risks.…”
Section: Remixing Meta-analysesmentioning
confidence: 99%
“…Based on the available evidence ( n = 4) ( 35 , 39 , 40 , 44 ), the results of the timed up and go test indicate a difference of −0.26 s (95% CI −0.66 to 0.14) between the multi-component exercise training group and the no exercise training group. In simpler terms, a combination of aerobic and resistance exercise ( 39 , 40 ), or aerobic and functional exercise ( 35 , 44 ), did not improve balance or reduce fall risks. Our cautious takeaway is that multi-component exercise training, in the absence of a dedicated balance exercise, is unable to effectively achieve both BP control and balance improvement simultaneously.…”
Section: Remixing Meta-analysesmentioning
confidence: 99%
“…In this context, several studies have already shown the benefits of an MTP on hemodynamic parameters [15,16] and functional capacity [17], as well as improvements in the lipid profile of older women [18,19]. Therefore, this type of training is recommended as a strategy to improve cardiovascular health [20] and physical functioning [21,22], and is advised for older adults in the long term [23,24]. Nonetheless, these individuals are often exposed to physical and behavioral factors [25], including seasonality [26], that result in greater risks of discontinuing an exercise habit.…”
Section: Introductionmentioning
confidence: 99%